2013
DOI: 10.1021/ma302229v
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Crystal Structures, Packing Behavior, and Thermal Stability Studies of a Homologous Series of n-Alkyl-Substituted Polyhedral Oligomeric Silsesquioxanes

Abstract: The homologous series of octa-n-alkylsilsesquioxanes (nalkylPOSS) was prepared by hydrosilylation of octahydrido-octasilsesquioxane H 8 T 8 with terminal n-alkenes in good yields (n = 2−18). The compounds were characterized by NMR spectroscopy ( 1 H, 13 C, 29 Si), MALDI−TOF and ESI MS. Most of them have also been characterized using X-ray crystallography, including some polymorphs. The packing systems of the octa-n-alkylsilsesquioxanes are reported. Two types of packing have been observed, rod-like and disk-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 41 publications
5
54
0
Order By: Relevance
“…From Figure 2A, during the heating of the PE-C 8 blend a small but relatively sharp melting peak at ~50 °C is observed. This corresponds directly to the melting temperature of the pure POSS T 8 C 8 cage system [28]. Hence, from this separate melting peak for PE-C 8 POSS blend it would be reasonable to suggest that the POSS is actually aggregated in crystals rather than well dispersed in the PE matrix.…”
Section: Thermal Propertiesmentioning
confidence: 81%
See 4 more Smart Citations
“…From Figure 2A, during the heating of the PE-C 8 blend a small but relatively sharp melting peak at ~50 °C is observed. This corresponds directly to the melting temperature of the pure POSS T 8 C 8 cage system [28]. Hence, from this separate melting peak for PE-C 8 POSS blend it would be reasonable to suggest that the POSS is actually aggregated in crystals rather than well dispersed in the PE matrix.…”
Section: Thermal Propertiesmentioning
confidence: 81%
“…Moreover, we have reported that these particular POSS systems, with long linear alkylchains, pack and crystallize in a lamellar fashion analogous to that of bulk n-alkanes [28][29][30].…”
Section: Thermal Propertiesmentioning
confidence: 98%
See 3 more Smart Citations